Physiological and biochemical changes in desiccation sensitive curry leaf (Murraya koenigii (L.) Sprengel) seeds - K. Raja, K. Arulmoorthy; Sundareswaran, S. (Journal of Phytology, 2019)
Curry leaf (Murraya koenigii (L.) Sprengel) is an important spice tree propagated by seeds. However, the seeds are sensitive to desiccation and considered as recalcitrant. Therefore, an experiment was conducted to analyze its level of desiccation and changes takes place during water loss. The results indicated that the reduction in seed moisture from 47.4 per cent leads to loss in viability. In which, the initial seed germination (100 %) declines slowly during desiccation and at the seed moisture content of 33.1 per cent it recorded 69 per cent germination at six days of exposure under ambient temperature (30±20C). Further moisture loss leads to drastic reduction in germination and hence, this could be the critical or lowest safe moisture content. In addition, the reduction in seedling vigour and enzymatic activity and increase in seed leachate were noticed during desiccation of the curry leaf seeds.